Triple-play services using different detection techniques for SAC-OCDMA systems - Al-Khafaji, Hamza M. R.; Aljunid, S. A.; Amphawan, Angela; Fadhil, Hilal A. (2012)
The development of many high bit-rate multimedia applications has emphasized the demand for service differentiation or prioritization techniques to ensure end-user quality-of-service (QoS) necessities. This paper focuses on utilizing different detection schemes in spectral-amplitude coding optical code-division multiple-access (SAC-OCDMA) systems to support 'triple-play' services (voice, video, and data) with diverse QoS requirements. The used subtraction detection techniques are complementary, AND, as well as modified-AND.Modified double-weight (MDW) codes are used as the signature codes for SAC-OCDMA systems.The simulation results show that modified-AND subtraction detection demonstrates better performance over other detection approaches.